Development and psychometric testing of a questionnaire for the Korea Youth risk behavior survey to assess physical activity behaviors - Bomi Park; Hye Ah Lee; Yoonhee Shin; Yeonjae Kim; Hyunjin Park; Seunghee Jun; Ui Jeong Kim; Kyungwon Oh; Sunhye Choi; Yangha Kim; Hyesook Park (BMC, 2024)
Abstract Background Physical activity is essential for physical, mental, and cognitive health. Providing evidence to develop better public health policies to encourage increased physical activity is crucial. Therefore, we developed an in-depth survey as part of the Korea Youth Risk Behavior Survey to assess the current status and determinants of physical activity among Korean adolescents. Methods We developed an initial version of the questionnaire based on a review of validated questionnaires, recent trends and emerging issues related to adolescent physical activity, and the national public health agenda pertaining to health promotion. Content validity was confirmed by a panel of 10 experts. Face validity was confirmed through focus group interviews with 12 first-year middle school students. The test-retest reliability of the questionnaire was evaluated by administering it twice, approximately two weeks apart, to a sample of 360 middle and high school students. Additionally, the frequency or average number of responses was analyzed in a sample of 600 students who participated in the initial test-retest reliability evaluation of the questionnaire developed in this study. Results Through item pool generation and content and face validity test, the final 15 questionnaire items were developed across five themes: levels of physical activity, school sports club activities, transportation-related physical activity, physical activity-promoting environments, and factors mediating physical activity. The test-retest reliability ranged from fair to substantial. Results from the newly developed survey reveal that only a minority of adolescents engage in sufficient physical activity, with only 17.2% and 21.5% participating in vigorous and moderate-intensity activities, respectively, for at least five days per week. Among school-based activities, 44.3% of students do not participate in school sports clubs due to reasons including absence of clubs and disinterest in exercise. The major motivators for physical activity are personal enjoyment and health benefits, whereas preferences for other leisure activities and academic pressures are the predominant barriers. Conclusions This study developed valid and reliable in-depth survey items to assess physical activity among Korean youths. It will hopefully enhance our understanding of adolescent physical activity, offering essential preliminary evidence to inform the development of public health strategies aimed at promoting adolescent health.